Epidemia de rumores: expresión de miedos, riesgos y desconfianza - Anna María Fernández-Poncela (Universidad Autónoma del Estado de México, 2014)
This text focuses on the review of some features of contemporary society: risk and uncertainty, the fear of humanity in general, and the culture of mistrust, particularly in Mexico. This is part of the precedents of the effervescence of rumors as a cultural and emotional story, the pandemic of ah1n1 flu in the year 2009 in Mexico. It is intended to show how rumors are the product of a concrete society and at the same time a social construction of said society. In this case, the result from specific existential and local ancestral fears and global contemporary risks: distrust in governmental authorities, fear of an American invasion and fear toward the international pharmaceutical industry are the most noticeable examples in this case study.